2015
DOI: 10.3389/fncel.2014.00442
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Alterations in Neocortex of Patients with Pharmacoresistant Temporal Lobe Epilepsy Can Explain the Comorbidity of Anxiety and Depression: The Potential Impact of Clinical Factors

Abstract: Temporal lobe epilepsy (TLE) is a chronic neurodegenerative disease with a high prevalence of psychiatric disorders. Temporal neocortex contributes to either seizure propagation or generation in TLE, a situation that has been associated with alterations of the γ-amino-butyric acid (GABA) system. On the other hand, an impaired neurotransmission mediated by GABA in temporal neocortex has also been involved with the pathophysiology of psychiatric disorders. In spite of these situations, the role of the necortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 62 publications
1
39
0
Order By: Relevance
“…The lower expression of both GABA B receptor subunits in TLE-HS compared to TLE-STG, could indicate a decline in GABA B receptors which would provide an explanation for the compromised GABA B functionality previously reported in pharmacological and electrophysiological studies in animal model and in human TLE (Billinton et al 2000;Princivalle et al 2002;Fürtinger et al 2003b;Mareš and Kubová 2015;Leung et al 2016;Rocha et al 2015). This may be affecting the formation of fully functional GABA B receptors: since the heterodimerisation of GABA B1 and GABA B2 in 1:1 stoichiometry is essential for receptor trafficking and G-protein activation, the GABA B2 subunit could be a potential target for the development of new agonists or activating transcription factors drugs, which may have a major clinical impact on the treatment of pharmaco-resistant TLE-HS patients.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
See 3 more Smart Citations
“…The lower expression of both GABA B receptor subunits in TLE-HS compared to TLE-STG, could indicate a decline in GABA B receptors which would provide an explanation for the compromised GABA B functionality previously reported in pharmacological and electrophysiological studies in animal model and in human TLE (Billinton et al 2000;Princivalle et al 2002;Fürtinger et al 2003b;Mareš and Kubová 2015;Leung et al 2016;Rocha et al 2015). This may be affecting the formation of fully functional GABA B receptors: since the heterodimerisation of GABA B1 and GABA B2 in 1:1 stoichiometry is essential for receptor trafficking and G-protein activation, the GABA B2 subunit could be a potential target for the development of new agonists or activating transcription factors drugs, which may have a major clinical impact on the treatment of pharmaco-resistant TLE-HS patients.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Previous studies reported impaired GABA B receptor mediated currents in TLE (Straessle et al 2003;Rocha et al 2015). This study aimed to examine possible differences in GABA B1a, GABA B1b and GABA B2 mRNA and protein expression.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Depression accounts for 30% of these disorders, followed by anxiety (10-25%), psychosis (2-7%), and personality disorders falling under 2% (Gaitatzis et al, 2004). In addition, neuropsychiatric conditions such as bipolar disorder, ADHD, and sleep disorders are also observed (Kimiskidis et al, 2007;Kanner, 2011;Rocha et al, 2014). Female gender, high seizure frequency, and a symptomatic epilepsy syndrome were identified as risk factors for the development of anxiety and/or depression in epilepsy patients (Kimiskidis et al, 2007).…”
Section: Emotional Changes In the Interictal Phasementioning
confidence: 99%